2022
DOI: 10.3389/fgene.2022.965070
|View full text |Cite
|
Sign up to set email alerts
|

Insight of vitellogenesis patterns: A comparative analysis of the differences between the primary and secondary vitellogenesis period in the ovary, hepatopancreas, and muscle of mud crab, scylla paramamosain

Abstract: The mud crab, Scylla paramamosain, has abundant nutrients in its edible parts, ovary, hepatopancreas, and muscle during the ovarian maturation stage. The ovary of S. paramamosain can re-mature after spawning during the secondary ovarian maturation period. We aimed to analyze the characteristics of the first vitellogenesis period (FVP)1 and second vitellogenesis period (SVP)2 of S. paramamosain during ovarian maturation to understand the differences in vitellogenesis patterns between the first and second ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…A previous study confirmed all mud crabs immediately after hatching were at the same starting point of the early vitellogenesis stage (stage III, ovarian color light-yellow) [53]. The ovarian stages in our study were distinguished as the early vitellogenesis stage (stage III, light-yellow) and the late vitellogenesis stage (stage IV, orange) [54,55], as confirmed by both morphology and histology.…”
Section: Tissue Collection and Histologysupporting
confidence: 90%
See 1 more Smart Citation
“…A previous study confirmed all mud crabs immediately after hatching were at the same starting point of the early vitellogenesis stage (stage III, ovarian color light-yellow) [53]. The ovarian stages in our study were distinguished as the early vitellogenesis stage (stage III, light-yellow) and the late vitellogenesis stage (stage IV, orange) [54,55], as confirmed by both morphology and histology.…”
Section: Tissue Collection and Histologysupporting
confidence: 90%
“…The 24 samples were hydrolyzed and extracted as previously described [54]. A total of 100 µL upper clear liquid was diluted by n-hexane to 1 mL and filtered by a 0.45 µ membrane.…”
Section: Gc-ms Analysis Of Fatty Acidsmentioning
confidence: 99%